Personality traits as determinants of political behavior: Ukrainian electoral and voting tendencies - Ivanchenko, Andreyanna; Ignatieva, Iryna; Lefterov, Vasiliy; Timchenko, Olexander; Іванченко, Андреянна Олексіївна; Иванченко, Андреянна Алексеевна (Romania. Journal "Studia Politica. Romanian Political Science Review", 2020)
Now there is a sharp increase of interest in politics, especially among young people. Meanwhile, the psychological mechanisms of the person’s political behavior (its manifesting and regulating), as well as interaction of his cognitive, emotional, motivation and value factors with the political system remain insufficiently studied. The aim of this research is to study the influence of personality traits on political behavior in order to find out the connection between person’s individual-psychological characteristics and the degree of his participation in political life within the territory of Ukraine. The Five-Factor «NEO-PI-R (NEO Personality Inventory-Revised)» model was used for analyzing the respondents’ tendency to politically significant behavior. The survey was conducted in 2017 in Ukraine (n=1247, age: 15-50 years). A positive correlation of the political participation indicators with the personal indicator Conscientiousness and the negative correlation with the Agreeableness parameter were revealed. We have established that emotionally balanced respondents more often show a desire to run for office and rarely participate in voting. High results for Agreeableness and Neuroticism determine the low level of political ambitions. These findings constitute a new step forward in understanding how personality traits form responses in the people’s political engagement while demonstrating the Ukrainian political tendencies.
Keywords: personality traits; political behavior; Five-Factor model; Big Five; NEO Personality Inventory-Revised